2021
DOI: 10.3389/fcimb.2021.750567
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio neptunius Produces Piscibactin and Amphibactin and Both Siderophores Contribute Significantly to Virulence for Clams

Abstract: Vibrio neptunius is an inhabitant of mollusc microbiota and an opportunistic pathogen causing disease outbreaks in marine bivalve mollusc species including oysters and clams. Virulence of mollusc pathogenic vibrios is mainly associated with the production of extracellular products. However, siderophore production is a common feature in pathogenic marine bacteria but its role in fitness and virulence of mollusc pathogens remains unknown. We previously found that V. neptunius produces amphibactin, one of the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Piscibactin has been reported from the fish pathogen Photobacterium damselae subsp. piscicida and from V. neptunius , where the production of piscibactin was shown to correlate with the pathogenicity of V. neptunius toward molluscs . Previous in silico analyses of Vibrio spp.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Piscibactin has been reported from the fish pathogen Photobacterium damselae subsp. piscicida and from V. neptunius , where the production of piscibactin was shown to correlate with the pathogenicity of V. neptunius toward molluscs . Previous in silico analyses of Vibrio spp.…”
Section: Resultsmentioning
confidence: 58%
“…genomes revealed that V. coralliilyticus has the genomic potential to produce piscibactin. 58,59 Indeed, six of the seven isolates in which piscibactin was detected in this study were identified as V. coralliilyticus, two of which are the putative coral pathogens OfT6−21 and OfT7−21. Thus, our data show that Vibrio spp.…”
Section: ■ Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Alternatively, a very highly stereoselective synthesis of the synepimer β-hydroxy acid 14 was carried out by diastereoselective reduction of tetramic acid 20 (Scheme 3). 35 Thus, the synthesis of the tetramic acid core was performed by the condensation of N-protected amino acid 10 (see Scheme 2) with Meldrum's acid in the presence of N-ethyl-N′- (3dimethylaminopropyl) In a parallel procedure, the trityl-protected (S)-α-azidocysteine methyl ester (25) was obtained from D-cysteine methyl ester (23) in two steps following a described method. 36,37 Thus, the thiol group of D-cysteine methyl ester (23) was protected with trityl to give amine 24, which was subjected to a diazo transfer reaction, using the electrophilically activated azide TfN 3 , NaHCO 3 as the base, and CuSO 4 as the catalyst, to afford azide 25 in a very good yield (86%) (Scheme 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…piscicida [ 6 ], Vibrio anguillarum [ 7 ] or V. ordalii [ 8 ]. Piscibactin production is also necessary for full virulence of the bivalve mollusks pathogen V. neptunius, and irp -HPI is present in the genome of other mollusks Vibrio pathogens of the Coralliilyticus clade [ 9 ]. Furthermore, irp -HPI is widespread among many other Vibrio spp., including human pathogens like V. cholerae [ 10 ].…”
Section: Introductionmentioning
confidence: 99%